(untitled) (Web of Teachers: Inderscience Research, 2025)
Language is not only a means of communication, but also a value. As long as language exists, world realities, spiritual and educational views, and traditions reach the next generation through written literature. The role of historical written sources in this regard is incomparable. The role of ancient written sources and monuments in determining the historical characteristics of the language in Uzbek linguistics is very important. Analyzing the linguistic characteristics of the rare work “Kutadgu Bilig”, written in the 11th century, helps to reveal the grammatical aspects of the current Uzbek literary language. This scientific article considers the grammatical and semantic characteristics of the language in “Kutadgu Bilig”, in particular, the components of phraseology that help to figuratively describe the plot of the work. The analysis studied the components of phraseology.